Responses of human skin in organ culture and human skin fibroblasts to a gadolinium-based MRI contrast agent: comparison of skin from patients with end-stage renal disease and skin from healthy subjects - DaSilva, Marissa; O'Brien Deming, Monica; Fligiel, Suzanne E G; Dame, Michael K; Johnson, Kent J; Swartz, Richard D; Varani, James (Investigative radiology, 2010)
Nephrogenic systemic fibrosis is a clinical syndrome occurring in a small subset of patients with end-stage renal disease (ESRD). Exposure to certain of the gadolinium-based contrast agents during magnetic resonance imaging appears to be a trigger. The pathogenesis of the disease is largely unknown. The present study addresses potential pathophysiologic mechanisms. We have compared responses in organ-cultured skin and skin fibroblasts from individuals with ESRD to responses of healthy control subjects to Omniscan treatment. Treatment of skin from ESRD patients with Omniscan stimulated production of matrix metalloproteinase-1 and tissue inhibitor of metalloproteinases-1, but not type I procollagen. The same treatment also stimulated an increase in hyaluronan production. Similar results were seen with skin from normal controls but basal levels were higher in ESRD patients. Fibroblasts in monolayer culture gave the same responses, but there were no differences based on whether the cells were isolated from the skin of healthy subjects or those with ESRD. These data indicate that Omniscan exposure alters an enzyme/inhibitor system responsible for regulating collagen turnover in the skin and directly stimulates hyaluronan production. The higher basal levels of type I procollagen, matrix metalloproteinase-1, tissue inhibitor of metalloproteinases-1, and hyaluronan in the skin from ESRD patients could contribute to the sensitivity of this patient population to fibrotic changes, which might be induced by exposure to some of the gadolinium-based contrast agents.